Answer:
Exelente calidad de programa
Answer:
f(x) = (x + 1)³ - (x + 1)² = x³ + 2 x² + x
Step-by-step explanation:
To shift g(x) to the left by one unit, replace all x in the expression of g(x) with (x + 1). How does this work? For example, g(x) = -2 for x = -1 in this question. f(x) = g(x + 1) may also equate -2, but only one unit to the left of x = -1 at x = -2 since -2 + 1 = -1. So is the case for the rest of the points on g(x). f(x) = g(x + 1) leads to the same set of values but only at one unit to the left. Adding one to the independent variable of g(x) shifts the graph to the left by one unit.
To find g(x + 1), replace every x in the equation x³ - x² with (x + 1):
f(x) = g(x + 1) = (x + 1)³ - (x + 1)².
Expand (x + 1)³ - (x + 1)² using the binomial theorem:
f(x) = (x + 1)³ - (x + 1)² = x³ + 3 x² + 3 x + 1 - (x² + 2 x + 1) = x³ + 2 x² + x
Answer:
f (x) = (x-1)^3 - (x-1)^2
Step-by-step explanation:
document.
Answer:
27
Step-by-step explanation:
jacob copies 30% of a document which is 8 pages
we can solve this using cross multiplication
30 % : 8
100% : x
30%x = 100%*8
30% x = 8
x = 8/ 30%
x = 26.667
to 2sf
Answer: The function shows by the table is cubic function.
Explanation: Since, the given values of the function are
f(x): –29 –10 –3 –2 –1 6 25
First difference: 19 7 1 1 7 19
Second difference: -12 -6 0 6 12
Third difference: 6 6 6 6
Since, here, the value in third difference is repeating to 6. Therefore, according to the definition of successive difference, equation must have three degree. So, it is a cubic equation.
Answer:
150 in
Step-by-step explanation:
there are 12 in in a foot. There are 12 feet so 12*12=144. Then you add 6 because half a foot is 6 in which will give you 150 in
Answer:
I think it is 150 inches. Please tell me if I am worng!!